The Corrosion of Financial System in Egypt and its Impact in Foreign Currency Commonality during the First Half of the Ninth Century A.H./the First Half of the Fifteenth Century A.D. - كَمـر مجيد رغيد (Al-Adab Journal, 2018)
The corrosion of financial system in Egypt during age of Al-Mamluks Fortress, in the first half of the fiftieth century A.D. because the bad policy of Sultans, and the commonality of faked money, bribery, and security in order to obtain important position including supervising the house of mintage, that opened the marketsfor foreign money to be popularity, especially money minted in Venice during Al-Mamluk Age, that money made with copper, it was considered the basis of dealing and price-fixing in the Islamic markets at that time. Prompting a number of Al-Mamluks Fortress Sulans to make attempts to reduce the popularity of foreign money